Evaluating the Psychological Effect of Orthodontic Treatment after 1 Year Using Psychosocial Impact of Dental Aesthetics Questionnaire in Indian Subjects: A Prospective Assessment - JK Sonia Bai; Sambhu Prasad; Nitu Dubey; Padma Panni; Awanindra K. Jha; Abhik Sinha (Journal of Pharmacy and Bioallied Sciences)
Background: The effect of dental malocclusion and management on functional and psychological wellbeing is a topic of interest. Aim: The study was conducted to assess the change in the psychological effect of malocclusion using PIDAQ (Psychosocial Impact of Dental Aesthetics Questionnaire) adopted for Indian subjects after 1 year of orthodontic treatment. Methods: The study assessed 186 subjects needing fixed orthodontic treatment where PIDAQ translated in Hindi was used after pretesting. All subjects were asked to answer the questionnaire at pretreatment and 1 year following treatment as T1 and T2. Also, IOTN (Index of Orthodontic Treatment Need) was used to assess self-perception and severity of malocclusion. Results: A statistically significant decrease in each factor and total PIDAQ score was seen after 1 year of treatment (P < 0.001). A positive association was seen between IOTN-AC (IOTN-Aesthetic Component) and psychological malocclusion impact. Conclusion: The psychometric PIDAQ scores instrument can be used as an OHRQoL (Oral Health-Related Quality of Life) assessment tool in Indian subjects for further research assessment.